Dehydroepiandrosterone Sulfate Reduces Acoustic Injury of the Guinea-Pig Cochlea - Keiji Tabuchi; Hidekazu Murashita; Tadamichi Tobita; Keiko Oikawa; Shigeki Tsuji; Isao Uemaetomari; Akira Hara (Elsevier, 2005)
The present study was performed to determine effects of dehydroepiandrosterone sulfate (DHEAS), a neurosteroid, on acoustic injury. Albino guinea pigs were exposed to a 2 kHz pure tone of 120 or 125 dB sound pressure level for 10 min immediately after intravenous administration of DHEAS. Statistically significant improvement in the compound action potential threshold shifts and in amplitude reduction of distortion-product otoacoustic emissions was observed 1 week after the acoustic overexposure in the animals treated with DHEAS. The present results suggest that DHEAS has a protective effect against acoustic injury of the cochlea. Keywords:: dehydroepiandrosterone sulfate (DHEAS), acoustic injury, cochlea